'But how do I teach them?': Autism & Initial Teacher Education (ITE). Issue 7 (3rd July 2018) - Ravet, Jackie
ABSTRACT: Many teachers are prepared for professional practice by attending Initial Teacher Education (ITE) courses in universities across the world. Under UK legislation, this preparation must equip teachers to address the needs of all children in mainstream classrooms, including learners on the autism spectrum – but does it? In this paper, I will critically explore this question by examining the findings of a research study focusing on a four-year ITE programme in a UK university. The research was designed using qualitative methods (online open-ended questionnaires and focus groups). The key findings were that the majority of students and tutors had some basic autism awareness, but little or no knowledge and understanding of autism teaching strategies. There was a consensus that teachers require both of these to ensure the inclusion of learners with autism in mainstream classrooms. Participants agreed there were currently insufficient inputs on autism on the ITE programme. This was related to a lack of tutor expertise, concerns about medical labelling and questions about ITE curriculum overload and priorities. Participants identified a range of ideas for improving autism education across the ITE programme which will be explored in the second phase of the study.